2022
DOI: 10.1093/plcell/koac037
|View full text |Cite
|
Sign up to set email alerts
|

CONSTITUTIVE EXPRESSER OF PATHOGENESIS-RELATED GENES 5 is an RNA-binding protein controlling plant immunity via an RNA processing complex

Abstract: Plant innate immunity is capable of combating diverse and ever evolving pathogens. The plasticity of innate immunity could be boosted by RNA processing. Arabidopsis thaliana CONSTITUTIVE EXPRESSER OF PATHOGENESIS-RELATED GENES 5 (CPR5), a key negative immune regulator, is a component of the nuclear pore complex. Here we further identified CPR5 as a component of RNA processing complexes. Through genetic screening, we found that RNA splicing activator NineTeen Complex and RNA polyadenylation factor CLEAVAGE AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…It was reported that the Arabidopsis ORC nucleoporin Nup85 physically interacts with a key Mediator component MED18, which is required for the expression of abscisic acid- and salt stress-responsive genes [ 66 ]. Recently, the plant-specific transmembrane nucleoporin CPR5 was identified as a novel RNA-binding protein and may work in the pre-mRNA splicing and polyadenylation complex to regulate plant immune induction [ 67 ]. We showed that the NB component GBPL3 recruits chromatin modifiers, core transcription apparatus, and various TFs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the Arabidopsis ORC nucleoporin Nup85 physically interacts with a key Mediator component MED18, which is required for the expression of abscisic acid- and salt stress-responsive genes [ 66 ]. Recently, the plant-specific transmembrane nucleoporin CPR5 was identified as a novel RNA-binding protein and may work in the pre-mRNA splicing and polyadenylation complex to regulate plant immune induction [ 67 ]. We showed that the NB component GBPL3 recruits chromatin modifiers, core transcription apparatus, and various TFs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Upon ETI, CPR5 releases SIM and SMR1, which activate E2F TFs to induce PCD [ 103 ]. Finally, CPR5 regulates alternative splicing (AS; Figure 1 L) via its RNA-binding activity [ 105 ]. Interestingly, the mRNA of the gene-silencing-related AGO1 and several AS regulators are among its targets, suggesting that apart from its own role in AS, it also indirectly affects gene silencing and AS [ 105 ].…”
Section: Regulation Of the Plant Immune Transcriptome Occurs At Multi...mentioning
confidence: 99%
“…Finally, CPR5 regulates alternative splicing (AS; Figure 1 L) via its RNA-binding activity [ 105 ]. Interestingly, the mRNA of the gene-silencing-related AGO1 and several AS regulators are among its targets, suggesting that apart from its own role in AS, it also indirectly affects gene silencing and AS [ 105 ]. In addition, Exportin-4 (XPO4) mediates nuclear export of TOPLESS-RELATED1 (TPR1), counteracting the translocation of TPR1 into the nucleus during ETI in the presence of high SA levels, as was studied in the cpr5 background [ 106 ].…”
Section: Regulation Of the Plant Immune Transcriptome Occurs At Multi...mentioning
confidence: 99%
“…Meanwhile, data from the cpr5 RNA-sequencing indicate that CPR5 participates in the regulation of alternative splicing (AS). Hence, CPR5 may act as a component of LLPS [ 68 ] which is involved in the plant immune response [ 69 ]. Collaboratively, NUP54, NUP58, NUP88, and XPO4 cooperate with CPR5 to regulate the disease resistance, highlighting that the integrity of the NPC plays pivotal roles in immune signals.…”
Section: Defensive Roles Of Npc In Plantsmentioning
confidence: 99%